Contributions of the axial spine to kicking biomechanics in the dipping kick among elite soccer players - Miller, E. M.; Bullock, G.; Waterman, B.; Nicholson, K.; O'Gara, T. (ISBS Proceedings Archive (Michigan), 2022)
The aim of this study was to develop normative data for thoracic, lumbar and pelvic range of motion (ROM) during a soccer dipping kick among five NCAA Division I and high-level youth soccer players, comparing successful and unsuccessful kicks. The "dipping" kick is a complex, skill whereby a player strikes the ball so that it initially rises, but due to its top spin subsequently "dips" toward the intended target. From a repeated measures, cross-sectional design, successful kicks had a lower thoracic rotation at ball contact and average maximum thoracic rotation at 31.1±26.5º compared to the average maximum value for unsuccessful kicks at 43.7±28.6º, although not statistically significant. This study suggests that twisting the thoracic spine away from the target in an effort to "whip" and dip the ball may be suboptimal. The thoracic spine is more in line with the pelvis in successful kicks.